Structural, electrical and optical properties of stoichiometric In2Te3 thin films. Issue 4 (March 2017) - Sowjanya, Vallem; Bangera, Kasturi V.; Shivakumar, G.K.
Abstract: In2 Te3 thin films were grown by thermal evaporation technique. The annealing of films played a major role to obtain stoichiometry, regardless of substrate temperature. Annealing at 300 ⁰C resulted in well oriented, mono-phased and nearly stoichiometric In2 Te3 thin films. The variation in grain size of In2 Te3 films associated with the substrate temperatures provides a significant control over the resistivity of the films, and the resistivity decreased with an increase in the grain size. The activation energy and optical band gap of stoichiometric In2 Te3 films were found to be 0.01±0.005 eV and 0.99±0.02 eV, respectively. The absorption co-efficient of these films was found to be of the order of 10 5  cm −1 .